Public sentiment towards economic sanctions in the Russia-Ukraine war - Vu M. Ngo; Toan L.D. Huynh; Phuc V. Nguyen; Huan H. Nguyen (Global Labor Organization (GLO), 2022)
This paper introduces novel data on public sentiment towards economic sanctions based on nearly one million social media posts in 109 countries during the Russia-Ukraine war by using machine learning. We show the geographical heterogeneity between government stances and public sentiment. Finally, political regimes, trading relationships, and political instability could predict how people perceived this inhumane war.
Keywords: F51; H77; 330; democracy; public sentiment; Russia-Ukraine